30 years of youth system of care lessons learned - a qualitative study of Hawaiʻi's partnership with the Substance Abuse and Mental Health Services Administration - Kelsie H. Okamura; David Jackson; Danielle L. Carreira Ching; Da Eun Suh; Tia L. R. Hartsock; Puanani J. Hee; Scott K. Shimabukuro (BMC, 2024)
Abstract Background The Hawaiʻi State Department of Health, Child and Adolescent Mental Health Division (CAMHD) has maintained a longstanding partnership with Substance Abuse and Mental Health Services Administration (SAMHSA) to enhance capacity and quality of community-based mental health services. The current study explored CAMHD's history of SAMHSA system of care (SOC) awards and identified common themes, lessons learned, and recommendations for future funding. Methods Employing a two-phase qualitative approach, the study first conducted content analysis on seven final project reports, identifying themes and lessons learned based on SOC values and principles. Subsequently, interviews were conducted with 11 system leaders in grant projects and SOC award projects within the state. All data from project reports and interview transcripts were independently coded and analyzed using rapid qualitative analysis techniques. Results Content validation and interview coding unveiled two content themes, interagency collaboration and youth and family voice, as areas that required long-term and consistent efforts across multiple projects. In addition, two general process themes, connection and continuity, emerged as essential approaches to system improvement work. The first emphasizes the importance of fostering connections in family, community, and culture, as well as within workforce members and child-serving agencies. The second highlights the importance of nurturing continuity throughout the system, from interagency collaboration to individual treatment. Conclusions The study provides deeper understanding of system of care evaluations, offering guidance to enhance and innovate youth mental health systems. The findings suggest that aligning state policies with federal guidelines and implementing longer funding mechanisms may alleviate administrative burdens.